The Systems of Technical Barriers to Trade of China and Mexico under the Framework of WTO - González García, Juan; Zhang, Juanjuan; Zamora Torres, América Ivonne (México y la Cuenca del Pacífico, 2017)
In 2009, a financial crisis swept the globe and the world economy entered the “Severe Winter Period” causing a significant decline in spite of the international trade or the transitional capital flow. In order to deal with the crisis, all countries issued a series of policies in an attempt to stimulate the economy into its recovery while, at the same time, they implemented a variety of trade measures, among which, Technical Barriers to Trade (TBT) was one of the main ones since it was focused in the protection of domestic economy, one aspect that has become a major obstacle for the recovery of the global economy, and the proposition of submitting the international trade system, whose main contents include a multilateral trading system and the rules of WTO, to a severe test. China and Mexico are both emerging economies affected by other countries’ TBT measures, especially China, who became one of the main victims of the current round of trade protectionism. Taking base on the analysis of the current global TBT status and the regulations of the WTO, the research will compare similarities and differences of TBT systems between China and Mexico, making recommendations to both nations in order for them to cope with the trade protectionism impact currently prevailing in the world. Los sistemas de barreras técnicas al comercio de China y México en el marco de la OMC En 2009, la crisis financiera azotó el mundo y la economía mundial entró en el “periodo de invierno severo” causando una caída significativa a pesar del comercio internacional o del flujo de capital transicional. Para hacer frente a la crisis, todos los países emitieron una serie de políticas para estimular la recuperación de la economía y, al mismo tiempo, implementaron una serie de medidas comerciales, entre las que se encuentran los barreras técnicas al comercio (BTC), siendo éstas de las principales, puesto que se centraron en la protección de la economía nacional, aspecto que se convirtió en un obstáculo importante para la recuperación de la economía global, y del envío de ésta al sistema del comercio internacional, cuyos principales contenidos incluyen al sistema de comercio multilateral y las reglas de la omc, sometiéndolos a una prueba severa. China y México son economías emergentes afectadas por las medidas BTC de otros países, especialmente China, que se convirtió en una de las principales víctimas de la actual ronda de proteccionismo comercial. Tomando como base el análisis de la actual situación mundial de btc y las re- gulaciones de la OMC, en la investigación se comparan similitudes y diferencias de los sistemas de btc entre China y México, haciendo recomendaciones a ambas naciones para que puedan hacer frente al impacto del proteccionismo comercial actualmente imperante en el mundo.